Arterial spin labeling clinical applications for brain tumors and tumor treatment complications: A comprehensive case-based review. Issue 2 (April 2023) - Luna, Licia P; Ahmed, Amara; Daftaribesheli, Laleh; Deng, Francis; Intrapiromkul, Jarunee; Lanzman, Bryan A; Yedavalli, Vivek
Arterial spin labeling (ASL) is a noninvasive neuroimaging technique that allows for quantifying cerebral blood flow without intravenous contrast. Various neurovascular disorders and tumors have cerebral blood flow alterations. Identifying these perfusion changes through ASL can aid in the diagnosis, especially in entities with normal structural imaging. In addition, complications of tumor treatment and tumor progression can also be monitored using ASL. In this case-based review, we demonstrate the clinical applications of ASL in diagnosing and monitoring brain tumors and treatment complications.